RANCANG BANGUN ALAT BANTU PEMASANGAN PEGAS STRIPPER PRESS TOOL DENGAN SISTEM HIDROLIK - Meri Rahmi; Yuliar Yasin Erlangga; Aida Mahmudah; Badruzzaman Badruzzaman; Felix Dionisius (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
A press tool is used to cut or form a thin plate into the desired shape with a pressing process or a press machine. One of the main things in the design of the press tool is the calculation for determining the type, size and, material of the spring. The spring in the press tool design is placed on the stripper as a pressure plate material before it is formed. The problem that often occurs in the design of the press tool is the initial force of the spring and the number of springs often have high values. This has an impact on the difficulty of the operator in installing the spring during assembly. The installation on the press machine requires more energy that exceeds the operator's power. This problem is often a challenge in itself both in terms of designing and manufacturing press tools. Assumptions and limitations of the problem of the design is 12,64 kN. This force is used for the educational practicum materials. Based on the design calculations the number of springs needed are 4 springs. While the hydraulic required is 10 tons. The results obtained based on simulation analysis using Solidworks software, show that with the number of springs and hydraulics calculated and based on the design form of the stripper installation tool, it is in the safe category.